CYSTATIN C, HbA1c, DAN RASIO ALBUMIN KREATININ - Juliani Dewi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Prevalence of type 2 diabetes mellitus and chronic kidney disease is increasing nowdays. Cystatin C is a more sensitive marker in detecting kidney disturbance at an early stage. Microalbuminuria indicates that there is an increasing risk in kidney disorders in diabetes mellitus patients. HbA1c is used to assess average blood glucose in three (3) months. An evaluation about the relation among Cystatin C, HbA1c, and ACR is needed to decide which test will be appropriate for the patient. Cystatin C was determined using Particleenhanced nephelometric immunoassay (PENIA) method from BN Prospec. High Performance Liquid Chromatography (HPLC) method from BioRad was used for HbA1c test, while random urine sample was used for Albumin Creatinine Ratio (ACR) test. Urine and serum creatinine were tested by immunoturbidimetric assay from Cobas C501. Correlation among Cystatin C, HbA1c, and ACR was estimated using Spearman’s correlation test. There was a significant correlation among Cystatin, HbA1c, and ACR. Spearman correlation value showed a positive weak correlation. There was a strong relation between Cystatin C and HbA1c, but weak relations between Cystatin C and ACR, and between HbA1c and ACR. It can be concluded that due to the weak correlation between ACR and kidney function as well as between ACR and HbA1c, ACR is not a good assessment to predict diabetic nephropathy progressiveness.